Pembelajaran Supervised SVM Untuk Identifikasi Obyek Pisau Pada Mesin X-Ray Bandara Juanda - Agung Santoso; Isturom Arif; M Hatta (NJCA (Nusantara Journal of Computers and Its Applications), 2016)
The detection process is started changing RGB image to YCbCr and then the canal Cb is chosen followed by 3processes consisting of making binary image, filtration and segmentation. The binary image aims to changeimage to white black, filtration is used to abolish noise, and segmentation is used to float object and dimensioncalculation consisting of RV and Σ pixel. After having its value, the process of SVM classification is done byusing data training and testing. The result of SVM process is graphic which will be used to identify a knife objector not.